2018
DOI: 10.1002/slct.201802943
|View full text |Cite
|
Sign up to set email alerts
|

Facile Surface Modification of Glass‐Fiber Membrane with Silylating Reagent through Chemical Bonding for the Selective Separation and Recycling of Diverse Dyes from Aqueous Solutions

Abstract: a] 3-(Trimethoxysilyl)-1-propanamine (APTMS) modified glass fiber membrane (APTMS-GF) was prepared via chemical bonding with different volume ratios (APTMS : methanol = 1:20, 1:10, 1:5), which was called APTMS-GF-1, À 2 and À 3, respectively. For congo red (CR) with the concentrations ranging from 5 to 45 mg L À 1 , the removal efficiencies were up to above 95% by filtration with APTMS-GF composite membranes, but there was no distinct difference in removal capacity with increasing the volume ratio of APTMS. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…GF was immersed in APTES (NH 2 (CH 2 ) 3 –Si(OCH 2 CH 3 ) 3 ) organic solution to fully hydrolyze APTES, as shown in ( Figure 3 B), forming APTES-modified GF [ 69 , 70 ]. Similarly, Li et al modified a GF membrane (GFM) with 3-(trimethoxy-methylsilyl)-1-propylamine (NH 2 (CH 2 ) 3 –Si(OCH 3 ) 3 , APTMS) to obtain APTMS-modified GF [ 64 ].…”
Section: Surface Modification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GF was immersed in APTES (NH 2 (CH 2 ) 3 –Si(OCH 2 CH 3 ) 3 ) organic solution to fully hydrolyze APTES, as shown in ( Figure 3 B), forming APTES-modified GF [ 69 , 70 ]. Similarly, Li et al modified a GF membrane (GFM) with 3-(trimethoxy-methylsilyl)-1-propylamine (NH 2 (CH 2 ) 3 –Si(OCH 3 ) 3 , APTMS) to obtain APTMS-modified GF [ 64 ].…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…Thomason reported that by modifying the GF surface with a silane coupling agent, a crosslinking layer formed on the GF surface, which appeared as “islands” instead of a continuous layer on the GF surface, resulting in an uneven structure ( Figure 3 C). Thus, the specific surface area increased [ 64 , 65 , 143 ]. Tomao soaked GF in 20% hydrochloric acid solution and studied the influence of the treatment time (4, 6, and 8 h) and temperature (40, 60, 80, and 100 °C) on the surface hydroxyl density on the GF.…”
Section: Characteristics Of Mgfmentioning
confidence: 99%
See 1 more Smart Citation